2013
DOI: 10.17221/51/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen and nitrogen species and hormone signalling in systemic infection of pea by Pea enation mosaic virus

Abstract: Kyseláková H., Sedlářová M., Kubala M., Nožková V., Piterková J., Luhová L., Novák O., Ilík P. (2013): Reactive oxygen and nitrogen species and hormone signalling in systemic infection of pea by Pea enation mosaic virus. Plant Protect. Sci., 49: 105-119.The physiological responses of pea plants during 40 days of compatible interaction with Pea enation mosaic virus (PEMV) were evaluated. PEMV induces systemic changes in the concentration of phytohormones. At 5 days post inoculation (dpi), a simultaneous increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that plants are able to protect against abiotic stress (Gill and Tuteja, 2010 ; Li et al, 2011 ) or biotic stress (Gonçalves et al, 2013 ; Kyseláková et al, 2013 ) by increasing the activities of antioxidant enzymes such as SOD, CAT, and POD. In the present study, we found that drought stress significantly increased the activities of SOD, POD, and CAT in both the healthy and diseased plantlets, but single virus infection increased slightly the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that plants are able to protect against abiotic stress (Gill and Tuteja, 2010 ; Li et al, 2011 ) or biotic stress (Gonçalves et al, 2013 ; Kyseláková et al, 2013 ) by increasing the activities of antioxidant enzymes such as SOD, CAT, and POD. In the present study, we found that drought stress significantly increased the activities of SOD, POD, and CAT in both the healthy and diseased plantlets, but single virus infection increased slightly the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The stock solution was diluted to 1 mM in 10 mM TRIS-HCl buffer. Later, the AgNPs and AgBulk diluted in distilled water were added to the solution (Baccelli et al, 2014;Grunberg and Taleisnik, 2015;Kyselakova et al, 2013;Zabala et al, 2015).…”
Section: Reactive Oxygen Species Analysismentioning
confidence: 99%
“…Although a positive correlation among chlorotic symptom development, the number of viral copies and the generation of hydrogen peroxide, reduced glutathione and pyridine nucleotides has been observed in SuCMoV‐infected sunflower , it is still not clear whether ROS causes the symptoms or is a result of symptom development during viral infection. It has been reported that low ROS concentrations lead to signal transduction and acclimation/defense responses , whereas high ROS levels lead to oxidation damage to lipids, DNA and proteins, and ultimately cell death . Therefore, monitoring ROS generation during symptom development is helpful in elucidating the mechanism of viral infection and symptom development based on ROS.…”
Section: Introductionmentioning
confidence: 99%